Beyond “for ever England”: Contemporary British Women’s War Poetry and the First World War Canon - Sofia Permiakova (Anglica. An International Journal of English Studies)
Turning to the First World War patriotic narrative of “for ever England,” epito- mised by Rupert Brooke and his writing as the point of departure, this paper investigates 21st century commemorative women’s poetry written during the First World War centenary years and its subversive interaction with this traditional war narrative. This article argues that while the public discourse on war memory often turned to the idea of a “shared past” between the UK and former colonies, thus “sanitising” the history of colonial violence (as argued by Santanu Das), poems by Yrsa Daley-Ward, Malika Booker, Imtiaz Dharker, and Jenny Lewis written for commemorative anthologies effectively de-colonise the nar- rative(s) of the First World War by opening up the space for new voices and construing the image of England beyond “for ever England” in its relation to other spaces and other wars.